Antagonistic paralogs control a switch between growth and pathogen resistance in C. elegans - Reddy,KC; Dror,T; Underwood,RS; Osman,GA; Elder,CR; Desjardins,CA; Cuomo,CA; Barkoulas,M; Troemel,ER (PLoS Pathogens, 2019)
Immune genes are under intense, pathogen-induced pressure, which causes these genes to diversify over evolutionary time and become species-specific. Through a forward genetic screen we recently described a C. elegans-specific gene called pals-22 to be a repressor of “Intracellular Pathogen Response” or IPR genes. Here we describe pals-25, which, like pals-22, is a species-specific gene of unknown biochemical function. We identified pals-25 in a screen for suppression of pals-22 mutant phenotypes and found that mutations in pals-25 suppress all known phenotypes caused by mutations in pals-22. These phenotypes include increased IPR gene expression, thermotolerance, and immunity against natural pathogens, including Nematocida parisii microsporidia and the Orsay virus. Mutations in pals-25 also reverse the reduced lifespan and slowed growth of pals-22 mutants. Transcriptome analysis indicates that pals-22 and pals-25 control expression of genes induced not only by natural pathogens of the intestine, but also by natural pathogens of the epidermis. Indeed, in an independent forward genetic screen we identified pals-22 as a repressor and pals-25 as an activator of epidermal defense gene expression. In summary, the species-specific pals-22 and pals-25 genes act as a switch to regulate a program of gene expression, growth, and defense against diverse natural pathogens in C. elegans.